Microservice Orchestration for Process Control in Industry 4.0 - Pontarolli, Ricardo P. [UNESP]; Bigheti, Jeferson A.; Fernandes, Michel M. [UNESP]; Domingues, Felipe O. [UNESP]; Risso, Sergio Luiz; Godoy, Eduardo P. [UNESP]; IEEE (Ieee, 2020)
New manufacturing applications in Industry 4.0 (I4.0) focus on the combination of industrial informatics and automation technologies, including the Industrial Internet of Things, Network Control Systems, Service Oriented Architectures and Cloud Computing. The great challenge of these applications is to promote the integration between these technologies, equipment and systems allocated at different hierarchical levels of industrial systems, making automation collaborative through the use and sharing of services. This paper focuses on the study, implementation and performance analysis of microservices orchestration for process control applications in I4.0. The Microservice-Oriented Architecture is described, as well as the development of microservices related to process control. The microservice orchestration is evaluated through experimental results considering a process control loop and the performance analysis of the service communication.
Keywords: service composition; service-oriented architecture; Industrial control systems; Moleculer framework